Establishment of a Novel Mouse Model for Atherosclerotic Vulnerable Plaque - Xueyu Wang; Xueyu Wang; Yahong Fu; Yahong Fu; Zulong Xie; Muhua Cao; Muhua Cao; Wenbo Qu; Wenbo Qu; Xiangwen Xi; Xiangwen Xi; Shan Zhong; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background and Aims: Acute coronary syndrome (ACS) is a group of clinical syndromes characterized by rupture or erosion of atherosclerotic unstable plaques. Effective intervention for vulnerable plaques (VP) is of great significance to reduce adverse cardiovascular events.Methods: Fbn1C1039G+/− mice were crossbred with LDLR−/− mice to obtain a novel model for atherosclerotic VP. After the mice were fed with a high-fat diet (HFD) for 12 or 24 weeks, pathological staining and immunohistochemistry analyses were employed to evaluate atherosclerotic lesions.Results: Compared to control mice, Fbn1C1039G+/−LDLR−/− mice developed more severe atherosclerotic lesions, and the positive area of oil red O staining in the aortic sinus was significantly increased after 12 weeks (21.7 ± 2.0 vs. 6.3 ± 2.1) and 24 weeks (32.6 ± 2.5 vs. 18.7 ± 2.6) on a HFD. Additional vulnerable plaque characteristics, including significantly larger necrotic cores (280 ± 19 vs. 105 ± 7), thinner fiber caps (14.0 ± 2.8 vs. 32.6 ± 2.7), apparent elastin fiber fragmentation and vessel dilation (3,010 ± 67 vs. 1,465 ± 49), a 2-fold increase in macrophage number (8.5 ± 1.0 vs. 5.0 ± 0.6), obviously decreased smooth muscle cell number (0.6 ± 0.1 vs. 2.1 ± 0.2) and an ~25% decrease in total collagen content (33.6 ± 0.3 vs. 44.9 ± 9.1) were observed in Fbn1C1039G+/−LDLR−/− mice compared with control mice after 24 weeks. Furthermore, spontaneous plaque rupture, neovascularization, and intraplaque hemorrhage were detected in the model mouse plaque regions but not in those of the control mice.Conclusions: Plaques in Fbn1C1039G+/−LDLR−/− mice fed a HFD show many features of human advanced atherosclerotic unstable plaques. These results suggest that the Fbn1C1039G+/−LDLR−/− mouse is a novel model for investigating the pathological and physiological mechanisms of advanced atherosclerotic unstable plaques.